Electricity Consumption and Associated Risks in European Countries - Convergence Analysis. (June 2018) - Szajt, M; Kucęba, R; Zawada, M; Kowalik, J
Abstract: Demand for electricity increases with economic development. At the same time, it is expected to provide the cleanest energy. This paper attempts to analyze the convergence of electricity consumption in European countries, reduce transmission losses and reduce the pollution associated with it - CO2. In the presented research European states were taken into account. All countries and individual European Union and non-EU unions were analyzed. The study used descriptive statistics and B-Convergence analysis. The aim of the study was to compare changes in these variables in the EU Member States and non-affiliated countries. The results indicate in general terms the convergence of both energy consumption and CO2 emissions reduction. Specific studies indicate that non-EU countries have no convergence in terms of energy consumption and reduction in transmission losses. The only significant convergence of CO2 emissions concerns. This may be due to financial constraints that inhibit the efficiency of the tested energy systems.